WOMEN EMPOWERMENT THROUGH PHYSICAL LIFE EDUCATION TATA BOGA IN FAMILY ECONOMIC EFFORT - Rita Uthartianty (IKIP Siliwangi Bandung, 2018)
This research is motivated by the limited access of women in supporting the family economy. Therefore the issues raised in this research is how to empower women through Life Skills Education (PKH) Culinary program in PKBM Jayagiri West Bandung Regency.The purpose of this study is to describe the initial condition of the learning community (women) before joining PKH Tata Boga programs, planning, implementation and results of the activities achieved, as well as supporting factors and inhibiting the implementation of activities. The theory that supports this research is about the concept of women empowerment, PKH, and family economy. While the research method used is qualitative descriptive approach. Research data obtained by observation, interview,and documentation.The results of the research are as follows: (1) The initial condition of the students to learn before joining the women's empowerment program through the PKH Tata Boga program is generally low family life with the limited entrepreneurship skill, (2) The planning of women empowerment through PKH Tata Boga program through the process of identification, mapping of potentials and resources as well as with the involvement of the learning community, (3) The process of implementing women's empowerment through the PKH Tata Boga program is carried out by various approaches and empowerment techniques with 80 percent proportion of practice and 20 percent theory, (4) women through the PKH program of culinary learners who are attained by citizens learn to have a change of attitude in utilizing the potential and leisure time to improve the family economy through the effort in the field of Culinary, (5) Supporting factors of activities such as studying citizens are not charged for learning, learning motivation,family, and society. While the inhibiting factors include limitations in marketing products, capital and partnerships. Keywords: Empowerment of women, Life Skills education (PKH), improvement of family economy